Implications of Low Muscle Mass across the Continuum of Care: A Narrative Review - Prado, Carla M. (Ann Med, 2018)
Abnormalities in body composition can occur at any body weight. Low muscle mass is a predictor of poor morbidity and mortality and occur in several populations. This narrative review provides an overview of the importance of low muscle mass on health outcomes for patients in inpatient, outpatient, and long-term care clinical settings. A one-year glimpse at publications that showcases the rapidly growing research of body composition in clinical settings is included. Low muscle mass is associated with outcomes such as higher surgical and post-operative complications, longer length of hospital stay, lower physical function, poorer quality of life, and shorter survival. As such, the potential clinical benefits of preventing and reversing this condition in patients are likely to impact patient outcomes and resource utilization/health care costs. Clinically viable tools to measure body composition are needed for routine screening and intervention. Future research studies should elucidate the effectiveness of multimodal modalities to counteract low muscle mass for optimal patient outcomes across the healthcare continuum.